PEMBELAJARAN TEKNIK DASAR SEPAK SILA PERMAINAN SEPAK TAKRAW MELALUI â€œHOOP TAKRAWâ€ PADA SISWA KELAS V SD NEGERI 3 JUNGSEMI KECAMATAN KANGKUNG KABUPATEN KENDAL (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The learning process is not maximized football precepts and yet achieve mastery in its implementation . Inaddition, students in the material value of sepak takraw especially football precepts still much below themaximum limit of completeness criteria ( KKM ) is 70 . The purpose of this research is to improve learningoutcomes through the basic techniques of soccer games sila " Hoop Takraw " . Research subjects in this studywere fifth grade students of SD Negeri 3 Jungsemi totaling 31 students .Research activities in each cycleincludes planning , implementation , observation , and reflection.Collection method is the method ofdemonstration and non- test ( observation and documentation ) . Analysis of the data used in this study isqualitative data in the form of data observation , field notes and documentation by analyzing the observationsheet that has been filled in learning .The results of this study showed the percentage of students to aspectsthrowing skills 45 % and 39 % on a rocking aspects of the learning cycle I considered completed . In the secondcycle increases is to be 100 % throwing skills and cradling aspect increased to 90 % . The average gradeachieved in the first cycle and rocking throwing skills by 74 % not 26 % complete and thorough . In the secondcycle the average classroom student skill increased to 100 % complete .